2005
DOI: 10.1093/ajcn/81.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial metabolic effects of regular meal frequency on dietary thermogenesis, insulin sensitivity, and fasting lipid profiles in healthy obese women1–3

Abstract: Regular eating has beneficial effects on fasting lipid and postprandial insulin profiles and thermogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
230
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(244 citation statements)
references
References 48 publications
9
230
1
4
Order By: Relevance
“…Irregular meal frequency was also associated with higher fasting total and LDL-cholesterol (P < 0·01) suggesting that the irregular meal routine appeared to produce a degree of impaired insulin resistance and higher fasting lipid profiles. In the obese women (BMI 37·1 (SD 4·8) kg/m 2 ), results were very similar to what was found in lean women, with no effect on fasting glucose and insulin, but peak insulin responses to a test meal lower after the regular meal pattern than after the irregular meal pattern (43) . In addition, the regular eating frequency was associated with lower energy intake, greater postprandial thermogenesis and lower fasting total and LDL-cholesterol (43) .…”
Section: Randomised Controlled Trialssupporting
confidence: 79%
“…Irregular meal frequency was also associated with higher fasting total and LDL-cholesterol (P < 0·01) suggesting that the irregular meal routine appeared to produce a degree of impaired insulin resistance and higher fasting lipid profiles. In the obese women (BMI 37·1 (SD 4·8) kg/m 2 ), results were very similar to what was found in lean women, with no effect on fasting glucose and insulin, but peak insulin responses to a test meal lower after the regular meal pattern than after the irregular meal pattern (43) . In addition, the regular eating frequency was associated with lower energy intake, greater postprandial thermogenesis and lower fasting total and LDL-cholesterol (43) .…”
Section: Randomised Controlled Trialssupporting
confidence: 79%
“…54 The regularity of meals has a positive impact on the homeostatic balance and the prevention of diseases. 55 Poor food intake with fast food, chips, biscuits, pasta, and other foods of low nutritional quality, or infrequency in the first meal of the day were related to higher BMI, hyperglycemia, and dyslipidemia. 55,56 Emotions are closely related to food.…”
Section: Interventions In Healthcare Environmentsmentioning
confidence: 99%
“…55 Poor food intake with fast food, chips, biscuits, pasta, and other foods of low nutritional quality, or infrequency in the first meal of the day were related to higher BMI, hyperglycemia, and dyslipidemia. 55,56 Emotions are closely related to food. Negative mood disorders such as anxiety, depression, anger, loneliness, abandonment, and unemployment, among others, can lead to an increase in the consumption of foods with high caloric density.…”
Section: Interventions In Healthcare Environmentsmentioning
confidence: 99%
“…However, other researchers have concluded that regular eating episodes can actually help with weight management and improve insulin sensitivity in obese women (Farshchi et al, 2005) and propose that the same would also be true for women with PCOS. Drummond et al (1998), using a similar methodology to the current study, reported that women in the general population had a mean of 4.4 eating episodes per day (excluding drinks), lower than the eating frequencies for women with PCOS reported here (five eating episodes per day (excluding drinks)).…”
Section: Recommendation For the Modification Of Dietary Fat Intakementioning
confidence: 99%